Multi-Channel Seismic Shot Data from the western North Atlantic Ocean (IPOD Line) acquired during R/V Gulf Seal expedition GS1974 (1974) (IEDA: Marine-Geo Digital Library, 2014)
This data set was acquired with a Multi-Channel Seismic system during Gulf Seal expedition GS1974 conducted in 1974 (Chief Scientist: Dr. John Grow; Investigator(s): Dr. John Grow and Dr. Rudi G. Markl). These data files are of SEGY format and include Multi-Channel Seismic Reflection shot data that have not been processed. Data were acquired as part of the project(s): International Phase of Ocean Drilling (IPOD) Site Survey, and funding was provided by NSF grant(s): UC-NSF-C482-2 scope F and USGS-XXX.